Wave and tidal power review - Kok, Nicolaas Johannes (Department of Civil Engineering, 2016)
A review of the technology of useful conversion of wave power and tidal power is presented. These two power resources are reviewed separately, but on the same basis: principles of operation, existing devices or plants and research and development. Promising wave power devices in Britain, the United States and Europe are discussed. If wave power is to be competitive, one of the first requirements may be energy densification. Proposed energy densification schemes include resonance, high pressure water and wave focussing. Wave focussing is a Norwegian invention, technically feasible, and although more research and development is required, it appears to be more promising than alternative forms of wave power utilisation. According to a preliminary cost analysis, it could be competitive with conventional hydro-electric power. The large scale exploitation of tidal power has been considered seriously for about half a century; the literature on the topic is voluminous. The main limitations of tidal power are its intermittent nature and the high costs involved in the construction of a plant. The existing pilot plants at the Rance and Kislaya Guba have respectively proved that tidal power is technically feasible and that construction costs could be reduced. With the rapid increase in the price of fossil fuels, tidal power plants may be realised at the two best sites in the world, the Bay of Fundy and the Severn Estuary.